Recent Advancements in Pulp Testing Devices - Akansha Kishen1 , Anjaneyulu2 , N. P. Muralidharan3 (Institute of Medico-legal Publications Pvt Ltd, 2020)
Pulp vitality test is very crucial in monitoring and regulating the state of health of a dental pulp, especiallyafter the case of traumatic injuries. The dental pulp is considered to be the innermost part of the tooth. It issurrounded on all sides with dentine except near the apical foramina. This hard dentine casting around thepulp protects it from infection by microbes present in the mouth. The traditional pulp testing methods involvethermal and electric pulp testing methods. This conventional method basically depends on the innervationand often yields or records either false positive or negative response. The newer pulp testing devices, some ofwhich are still under developmental stage, detect the blood supply of the pulp, enumerate pulpal vasculature,check the vitality of the tooth etc. These newer technologies function by light absorption and reflectionmethods in. They are considered to be more accurate and non-invasive methods. The review article attemptsto discuss the recent advancements in various pulp testing devices related to pulp vitality testing in clinicalendodontic practice. It also describes the principle on which these newer pulp testing devices are basicallybased on its mode of working. The aim of this review paper is to highlight the difference between sensitivitytesting and vitality testing.